Effect of High Peroxide Value Fats on Performance of Broilers in a Normal Immune State - McGill, J.; McGill, E.; Kamyab, A.; Firman , J.D. (International Journal of Poultry Science, 2011)
A floor pen trial was conducted to determine the effect of high peroxide value fats on performance of broilers in a normal immune state. Ross 708 Broilers were randomly assigned to 48 floor pens with each pen contained 30 birds. Dietary treatments were developed in a 3 x 2 factorial using three levels of fat rancidity, Peroxide Value (PV) of 0, 75 and 150. One half of each peroxide value diet also received an antioxidant at 125 ppm. Six dietary treatments with eight replicates were fed to broilers from hatch to day 49. Diets were formulated based on standard industry diets with the exception of fat being forced into the diet at 3% for the starter ration (0-3 wks), 6% in the grower ration (3-5 wks) and 6% in the finisher ration (5-7 wks). The trial measured the performance of the broilers based on the parameters of Feed Intake (FI), Weight Gain (WG) and feed conversion (F:G). An initial pen weight was taken on day 0 for each of the 48 pens and birds were weighed at 3, 5 and 7 weeks of age to calculate FE. At week 7, four birds per pen (32 birds/treatment) were sacrificed and processed in order to obtain a fat pad weight, carcass weight and percent meat yield. The results indicated that diets with a peroxide value of 75 or greater result in poorer feed conversion than the treatment with a peroxide value of 0. Furthermore, the addition of an antioxidant to the diets with a peroxide value of 75 or greater yielded a numerically improved feed conversion over the diets with the same peroxide value but no antioxidant.